Proceedings of the 29th ACM/IEEE International Conference on Automated Software Engineering 2014
DOI: 10.1145/2642937.2642975
|View full text |Cite
|
Sign up to set email alerts
|

Understanding performance stairs

Abstract: How do experts navigate the huge space of implementations for a given specification to find an efficient choice with minimal searching? Answer: They use "heuristics" -rules of thumb that are more street wisdom than scientific fact. We provide a scientific justification for Dense Linear Algebra (DLA) heuristics by showing that only a few decisions (out of many possible) are critical to performance; once these decisions are made, the die is cast and only relatively minor performance improvements are possible. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Details go beyond the scope of this paper. What is important is that in a study that explores the design space that is created [28], it is shown that the design decision that has the greatest impact on performance is what algorithm from the family of algorithms to use.…”
Section: How Do We Choose the Best?mentioning
confidence: 99%
“…Details go beyond the scope of this paper. What is important is that in a study that explores the design space that is created [28], it is shown that the design decision that has the greatest impact on performance is what algorithm from the family of algorithms to use.…”
Section: How Do We Choose the Best?mentioning
confidence: 99%
“…Dataflow programs (DfP) abound in today's world. They are fault-tolerant servers [14,46], relational query execution plans [20,46], dense linear algebra kernels [39,38], virtual instruments [53, 49,26], stream processing applications [26,54], and large-scale cloud data processing applications [13,25]. A Df P is a directed graph: nodes called boxes are components or computations; edges indicate the flow of data.…”
Section: Introductionmentioning
confidence: 99%
“…Reverse engineering legacy systems to extract and systematize the transformations (knowledge) used to build them is only the first step of a larger process. The knowledge gathered and encoded can later be used to mechanize/automate forward engineering [39,38], i.e., to generate new programs. Extensions provided a mechanism to ease the process of extracting knowledge from legacy systems, and allowed us to improve the tools to assist experts in this task.…”
Section: Introductionmentioning
confidence: 99%